The CFA Franc Zone : Currency Union and Monetary Standard - Boughton, James (IMF Working Papers; Working Paper ;, 1991)
The CFA franc zone comprises a group of countries in central and west Africa whose currencies have been firmly linked to the French franc since 1948. It combines the features of a currency union with those of an exchange rate peg, and an analysis of its effectiveness must examine both dimensions. Viewed from the perspective of a currency union among the African countries, it would appear that the zone would not constitute an optimum currency area. But when France is viewed as an integral part of the system, the benefits-including discipline, credibility, and stability in international competitiveness-become clearer.